VD_FINDINFO Jug / 2012 / 336 vom 30. Juli 2012 - VD Tribunal cantonal (2012)
INSOUMISSION À UNE DÉCISION DE L'AUTORITÉ, CONTRAVENTION, PROCÉDURE ÉCRITE | 292 CP, 398 al. 4 CPP (CH), 406 al. 1 let. c CPP (CH)